Anti-proliferative effect of the extracts and essential oil of Pimpinella anisum on gastric cancer cells - Samaneh Rahamoz-Haghighi; Malek Hossein Asadi (Shahrekord University of Medical Sciences, 2016)
Introduction: One of the most important fields to find the new drugs for combating cancers is herbal medicine and in this regard, attention to plant components against cancer has been increased nowadays. In the present study, we investigated the cytotoxic effect of alcoholic extracts and essential oil of Pimpinella anisum on viability of gastric cancer cell line (AGS) and angiogenesis of HUVEC cells . Methods: The alcoholic extracts and essential oil were obtained by soxhlet and Clevenger set, respectively. The viability of cells which treated with the extracts and the essential oil were assessed by MTT assay. In vitro tube formation assay was performed to assess the effect of the extracts and essential oil on angiogenesis potential of HUVEC cells. Results: The growth of AGS cells was inhibited by extracts and essential oil of Pimpinella anisum. Furthermore, the extracts and essential oil had inhibitory effects on the angiogenesis in HUVEC cells. The ethanolic extract inhibited cell proliferation of the AGS cells in 30 μg/mL at 48 hours after treatment but it had no significant effect on fibroblast cells. The inhibitory effect of methanolic extract was much better than the ethanolic extract at the same concentrations. The essential oil of the plant had the highest inhibitory effect on cancer cells compared with the alcoholic extracts. Conclusion: Therefore, our results showed that the alcoholic extracts and essential oil of Pimpinella anisum have antiprolifertion properties on gastric cancer cells and could be used as plant-based cures for gastric cancer.